Mechanochemical reactions of cocrystals: comparing theory with experiment in the making and breaking of halogen bonds in the solid state. Issue 59 (23rd June 2020) - Arhangelskis, Mihails; Topić, Filip; Hindle, Poppy; Tran, Ricky; Morris, Andrew J.; Cinčić, Dominik; Friščić, Tomislav
Abstract : The interconversions of halogen-bonded cocrystals exhibiting three different stoichiometries were predicted by different types of dispersion-corrected density functional theory (DFT) calculations and predictions experimentally validated by mechanochemistry. Abstract : Mechanochemical re-investigation of the halogen-bonded cocrystallisation of 1, 4-diazabicyclo[2.2.2]-octane and 1, 2-diiodotetrafluorobenzene revealed an unexpectedly complex system with three distinct cocrystal compositions, one of which also exhibits temperature-dependent polymorphism. This provided an opportunity to experimentally test the ability of dispersion-corrected periodic density functional theory (DFT) to not only explain the formation, but also predict the interconversion between halogen-bonded cocrystals of different stoichiometries.